Direct Ethanol Production from Lignocellulosic Sugars and Sugarcane Bagasse by a Recombinant Trichoderma reesei Strain HJ48. (2nd June 2014) - Huang, Jun; Chen, Dong; Wei, Yutuo; Wang, Qingyan; Li, Zhenchong; Chen, Ying; Huang, Ribo
Abstract : Trichoderma reesei can be considered as a candidate for consolidated bioprocessing (CBP) microorganism. However, its ethanol yield needs to be improved significantly. Here the ethanol production of T. reesei CICC 40360 was improved by genome shuffling while simultaneously enhancing the ethanol resistance. The initial mutant population was generated by nitrosoguanidine treatment of the spores, and an improved population producing more than fivefold ethanol than wild type was obtained by genome shuffling. The results show that the shuffled strain HJ48 can efficiently convert lignocellulosic sugars to ethanol under aerobic conditions. Furthermore, it was able to produce ethanol directly from sugarcane bagasse, demonstrating that the shuffled strain HJ48 is a suitable microorganism for consolidated bioprocessing.